2020
DOI: 10.1016/j.puhe.2020.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Late diagnosis of chronic liver disease in a community cohort (UK biobank): determinants and impact on subsequent survival

Abstract: BACKGROUND: Chronic liver disease (CLD) is frequently diagnosed at a late stage when prognosis is poor. We aimed to determine the patient factors associated with a late CLD diagnosis and its subsequent impact on survival in order to support early diagnosis initiatives. METHODS: We identified participants of UK biobank (UKB) study who developed first-time advanced CLD within 5-years. We identified factors associated with late diagnosis via logistic regression, and used survival analysis to measure the associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…New precision medicine strategies are needed in community settings to reduce late diagnosis of CLD. [2][3][4] Hitherto studies have mainly focused on developing diagnostic algorithms for significant/severe liver fibrosis. Here, we explore the potential for bringing a "QRISK3" paradigm to CLD, where a patient's individualised risk of a complication event is directly estimated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…New precision medicine strategies are needed in community settings to reduce late diagnosis of CLD. [2][3][4] Hitherto studies have mainly focused on developing diagnostic algorithms for significant/severe liver fibrosis. Here, we explore the potential for bringing a "QRISK3" paradigm to CLD, where a patient's individualised risk of a complication event is directly estimated.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most notable hallmarks of CLD is that it is usually not diagnosed until patients present with complications from cirrhosis; at which point, treatment options are limited and prognosis is irreversibly poor. 2 In this scenario, earlier diagnosis of CLD could allow clinicians to act sooner to prevent liver related mortality. 3,4 However, this must be weighed against the potential for unnecessary intervention (e.g.…”
Section: Performance Of Routine Risk Scores For Predicting Cirrhosis-...mentioning
confidence: 99%
See 1 more Smart Citation
“…254 Moreover, it has been clearly shown that late diagnosis of chronic liver disease was associated with aetiology; the odds of a late diagnosis were 12 times higher for an individual with alcohol-related liver disease than for an individual with viral hepatitis. 255 These results point towards the crucial importance of early diagnosis as interventions become less effective and more expensive when people with unhealthy alcohol consumption have already developed cirrhosis. 26,256 From this perspective, the range of targets of existing liver-related case-finding programmes appears too narrow.…”
Section: Moving From Treatment Of Complications To Case-finding Scree...mentioning
confidence: 99%
“…Liver disease causes no symptoms in its earlier stages; over half of patients have liver disease first diagnosed after an emergency hospital admission at a stage when the scope of any medical or behavioural intervention is minimal [ 1 , 2 , 11 ]. ArLD is 12 times more likely to present late compared to other aetiologies of liver disease [ 12 ]. Once patients with alcohol misuse develop cirrhosis, the prognosis becomes exceptionally poor; the mortality rate for alcohol-related cirrhosis has been reported as high as 75% at 5 years and 91% at 15 years [ 13 ].…”
Section: Introductionmentioning
confidence: 99%